(untitled) (Revista de Estudos da Linguagem, 2024)
The present perfect in Spanish is a verb form that can convey different aspect values in the sentence. The expression of these values, as well as their alternation with the simple past, differs considerably among Spanish varieties. Thus, in this work, we sought to verify how teaching materials address this issue in the description of the present perfect for learners of Spanish as a foreign language. To this end, three volumes of the Español Lengua Viva and Aula Internacional collections were analyzed. The results indicated that, in both collections, the description of the aspectual values of experiential perfect and perfect of recent past is privileged. In addition, the alternation between simple past and present perfect is approached in a dichotomous way, in which the first form is described as carrying the perfective aspect and the second, the perfect aspect, without any information about the linguistic variation involving such morphologies. It was argued that the description present in these materials does not reflect the linguistic reality of Spanish and gives the learner a false idea of the homogeneity of the language